Government Budget: Good Governance and Human Capital for Poverty Alleviation in Central Java - Agus Arifin; Rakhmat Priyono; Goro Binardjo (Universitas Muhammadiyah Purwokerto, 2025)
Good governance can be reflected in an integrated and clean system, supported by adequate quality human resources in achieving organizational goals (government, private, etc.) effectively and efficiently. One of the main goals of successful development is to improve community welfare, one indicator of which is reduced poverty (SDG number 1). To realize this goal, government budget allocation is needed for poverty alleviation. This research aims to analyze good governance and the quality of human resources in managing the poverty alleviation budget. The research method used is multiple regression with poverty as the dependent variable. The independent variables representing the budget are local own-source revenue (LOSR), fiscal balance (FB), capital expenditure (CE), social aid (SA), while the independent variable representing the quality of human resources is the human development index (HDI). The results show that (1) from the budget side, LOSR, FB, and SA can reduce poverty, while CE has no effect; (2) from the quality of human resources, HDI HDI is not strong enough to influence poverty even though the direction of its influence is appropriate.. The implications are: (1) From the revenue side, LOSR and FB, can be important variables for poverty alleviation, but they must be managed with good, clean, and correct budgets; (2) From the expenditure side, only SA can be a variable for poverty alleviation, but its influence is very small, so it needs better management; (3) The human development index remains an important variable in proper budget management to address poverty, but it takes longer to develop higher quality and competent human resources.